PROFILE OF PEDAGOGICAL CONTENT KNOWLEDGE ABILITIES OF PRE-SERVICE STUDENTS - Arya Wulandari, I Gusti Ayu Putu; Ida Ayu Made Wedasuwari; Wardana, I Ketut; Ilia Gustutus Dewi Fajar; Antara Jaya, I Gede (Jurnal Santiaji Pendidikan (JSP), 2025)
This study aims to describe the profile of Pedagogical Content Knowledge (PCK) abilities among in-service Teacher Professional Education (TPE) students at Mahasaraswati University in Denpasar. A descriptive research method utilizing a survey technique was employed, gathering data through an online Knowledge Test Simulation (KTS) available at https://simulasiup.unmas.ac.id/. The sample comprised 148 TPE students across five fields of study: Indonesian, English, Mathematics, History, and Biology. Data analysis was based on UP simulation scores, which assessed five components of PCK: knowledge of teaching strategies, content knowledge, understanding of students, curriculum knowledge, and evaluation knowledge. The results indicated that most students exhibited a moderate level of Pedagogical Content Knowledge (PCK), with an average score of 41.32 out of a possible 80. Scores varied significantly, ranging from a maximum of 80 to a minimum of 0. Approximately half of the students (50%) fell into the moderate category, while 20% achieved a high category and 5% reached a very high level of PCK. Conversely, 15% were classified as low, and 10%  as deficient. The analysis revealed that students' primary challenges lie in effectively integrating content knowledge with pedagogical techniques and developing appropriate student assessments. The study concludes that, although some students demonstrate strong mastery of PCK, the majority require additional support in enhancing their teaching strategies and assessment skills.